Fish distribution in the Ba Che and Tien Yen rivers - Thuy, Ta Thi; Hau, Tran Duc; Huan, Nguyen Xuan; Long, Pham Van (Academia Journal of Biology, 2020)
The ichthyo-fauna in the Ba Che and Tien Yen rivers, northern Vietnam is highly diverse, with a total of 245 species determined. However, data on the distribution of fish species are not sufficiently provided for the whole area. This study was conducted from 2008 to 2011 at 27 stations from the Ba Che and Tien Yen river basins to determine the distribution of fish species according to different sections of the rivers, water bodies, seasons, and salinity levels. The results show that fish species are distributed mainly in the river (with 210 species), concentrated in the downstream area (with 213 species). Fishes are mainly collected in the dry season when the salinity level of river is high, due to seawater intrusion which also brings in 160 species of marine fish. This shows that fish distribution in the research areas is mainly dominated by the presence of marine species. While for freshwater fish, it is clearly affected by the mountainous features. Apart from the common characteristics sharing between the two river basins, but the number of both freshwater and marine fish species in the Tien Yen river are larger than those of Ba Che river, which is related to fresh water surface, river morphology, the width and location of the estuary to the sea. The downstream area is home to the fish species recorded in the Red Data Book of Vietnam and the complementary species for Vietnam, while the middle and upstream of the rivers may offer a high potential of biodiversity, with many possibly new species for science. These are important data for the conservation and sustainable development of fish resources in the Ba Che and Tien Yen river basins.